2021
DOI: 10.7759/cureus.20786
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Extramedullary Multiple Myeloma Presenting As Acute Liver Failure

Abstract: Extramedullary spread of multiple myeloma was thought to be uncommon but with recent advancements in imaging and increased patient survival, the incidence of the extraosseous disease has risen in living individuals. Despite this, the extraosseous spread of multiple myeloma has been under-diagnosed and under-reported. Timely diagnosis of this extraosseous disease is clinically important, as it indicates a more aggressive disease variant and carries a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The study concluded that both types of heart failure were associated with an increased risk of acute respiratory failure and invasive and noninvasive mechanical ventilation. 6 Our study also revealed an elevated risk of acute coronary syndrome in this population, emphasizing the intricate interplay between immune thrombocytopenia and cardiovascular events. Govender et al conducted a retrospective investigation utilizing national population data from the United Arab Emirates (UAE) to examine the risk of mortality and cardiovascular events within this population.…”
Section: Discussionsupporting
confidence: 59%
“…The study concluded that both types of heart failure were associated with an increased risk of acute respiratory failure and invasive and noninvasive mechanical ventilation. 6 Our study also revealed an elevated risk of acute coronary syndrome in this population, emphasizing the intricate interplay between immune thrombocytopenia and cardiovascular events. Govender et al conducted a retrospective investigation utilizing national population data from the United Arab Emirates (UAE) to examine the risk of mortality and cardiovascular events within this population.…”
Section: Discussionsupporting
confidence: 59%